Niat menerapkan perizinan Bisnis Kuliner bagi UMKM Indonesia: Bukti dari Pekerja Migran Indonesia di Singapura - Marsudi Endang Sri Rejeki; Retty Ikawati; Dini Yuniarti (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
Migrant workers in Singapore benefit from a good business regulatory system. Regulations imposed require SMEs in Singapore to obtain a business permit before being allowed to operate. This research aims to determine whether the attitudes, social norms and behavioral control of migrant workers can influence them in carrying out culinary businesses oriented towards business permits when they return to Indonesia. In this research, the permits required include NIB (Business Identification Number), and PIRT (Food Production Registration). Research Methods: The approach used is a quantitative method, sourced from primary data of Singapore migrant workers, and Smart PLS is used to analyze the data. Research findings show that migrant workers have the intention to implement good business systems and regulations by fulfilling all NIB, and PIRT requirements in the future will doing business in Indonesia. The results of this research show that there are positive attitudes, subjective norms, and behavioral control among migrant workers when they return to Indonesia. Based on the research to recommended that in the future all retired Indonesian Migrant Workers can become independent entrepreneurs with capital from working for several years as PMI. starting business activities are planned well, with an appropriate business plan accompanied by complete business permits.